Management of Academic Supervision Based on Ruang GTK Platform to Improve Teacher Professional Competence (A Descriptive Qualitative Study at SDN Sukawangi and SDN 068 Cimincrang) - Rudi Setiawan; Nandang Koswara (Journal of Science and Education (JSE), 2026)
This study explores the implementation of digital-based academic supervision through the Ruang GTK platform by employing the Plan–Do–Check–Act (PDCA) cycle and its contribution to improving teacher competence at SDN Sukawangi and SDN 068 Cimincrang. The study is motivated by the need for a more transparent, systematic, and technology-enabled supervision model to meet contemporary quality-assurance demands in basic education. A descriptive qualitative case-study design was used. Data were collected through interviews, classroom observations, and document analysis during the first semester of the 2024/2025 academic year, involving principals and teachers as key informants. Data were analyzed thematically following the PDCA stages. The findings show that supervision planning was carried out systematically in Ruang GTK, including digital scheduling and use of standardized instruments; implementation combined face-to-face classroom observation with digital feedback, although several teachers still faced technical and digital-literacy constraints; the evaluation stage emphasized teacher reflection and strengthened transparency, but participation levels varied; and the follow-up stage took the form of targeted training, coaching, and monitoring, ensuring continuity of the PDCA cycle. The study concludes that integrating Ruang GTK with PDCA not only reinforces accountability in supervision but also supports teachers’ continuous professional development. Practically, the study encourages school leaders, teachers, and policymakers to optimize digital supervision as an instrument for improving teacher competence and educational quality.